Unexpected high 35S concentration revealing strong downward transport of stratospheric air during the monsoon transitional period in East Asia. Issue 5 (12th March 2016) - Lin, Mang; Zhang, Zhisheng; Su, Lin; Su, Binbin; Liu, Lanzhong; Tao, Jun; Fung, Jimmy C. H.; Thiemens, Mark H.
Abstract: October is the monsoon transitional period in East Asia (EA) involving a series of synoptic activities that may enhance the downward transport of stratospheric air to the planetary boundary layer (PBL). Here we use cosmogenic 35 S in sulfate aerosols ( 35 SO4 2− ) as a tracer for air masses originating from the stratosphere and transported downward to quantify these mixing processes. From 1 year 35 SO4 2− measurements (March 2014 to February 2015) at a background station in EA we find remarkably enhanced 35 SO4 2− concentration (3150 atoms m −3 ) in October, the highest value ever reported for natural sulfate aerosols. A four‐box 1‐D model and meteorological analysis reveal that strong downward transport from the free troposphere is a vital process entraining aged stratospheric air masses to the PBL. The aged stratospheric masses are accumulated in the PBL, accelerating the SO2 transformation to SO4 2− . Implications for the tropospheric O3 budget and the CO2 biogeochemical cycle are discussed. Key Points: The highest 35 S concentration ever measured for natural sulfate aerosols is reported Strong downward transport from the FT in October brings aged stratospheric air to the PBL Temporal variations in surface O3 in spring and autumn are in tandem with 35 SO4 2− concentrations